2021
DOI: 10.1210/clinem/dgab190
|View full text |Cite
|
Sign up to set email alerts
|

Cranial MRI Abnormalities and Long-term Follow-up of the Lesions in 770 Girls With Central Precocious Puberty

Abstract: Context Central precocious puberty(CPP) may arise from central nervous system(CNS) lesions in a few affected girls. Recently, the incidence of girls with CPP has increased mostly in 6-8 year-olds, in whom the necessity of magnetic resonance imaging(MRI) is debated. Objective To investigate the frequency, long-term outcome and potential predictors of CNS lesions in a large cohort of girls with CPP. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Using a BMI Z-score cutoff of > 0.5, they found no significant association (positive or negative) between BMI and risk of CNS abnormalities [ 68 ]. Although the number of individuals with CNS findings in this study was small, similar studies have also found no difference in BMI SDS between girls with CPP and normal vs abnormal imaging [ 67 , 71 , 74 ]. In fact, none of these studies identified any strong clinical or biochemical predictors of CNS abnormalities and therefore continued to recommend routine imaging in girls younger than 8 years.…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 48%
See 1 more Smart Citation
“…Using a BMI Z-score cutoff of > 0.5, they found no significant association (positive or negative) between BMI and risk of CNS abnormalities [ 68 ]. Although the number of individuals with CNS findings in this study was small, similar studies have also found no difference in BMI SDS between girls with CPP and normal vs abnormal imaging [ 67 , 71 , 74 ]. In fact, none of these studies identified any strong clinical or biochemical predictors of CNS abnormalities and therefore continued to recommend routine imaging in girls younger than 8 years.…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 48%
“…Indeed, younger age is the strongest predictor of CNS pathology, and MRI is routinely recommended in all girls younger than 6 years [ 69 , 70 ]. The benefit of neuroimaging in girls with CPP older than 6 years of age remains controversial, with some studies in support [ 11 , 67 , 71 ] and other studies against routine MRI [ 63 , 65 , 70 , 72 , 73 ].…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
“…4 The fact that the median age of treatment in the USA is 9 years and 11.6%-15% of the cases in whom treatment is initiated are younger than 8 years and the median age of 770 girls in whom treatment is initiated in a multicenter study in Turkey is 7.9 ± 1.35 years suggests that the majority of the cases in whom GnRHa treatment is initiated are between 7 and 9 years of age and mostly in the 8-9 age group. 2 , 5 In addition, recent reports from Turkey and Denmark confirm that the majority of the cases in whom treatment was initiated were in the idiopathic group. 5 , 6 …”
mentioning
confidence: 99%
“…2,3) Several researchers have reported the prevalence of CNS abnormalities detected on brain MRI in CPP. [4][5][6] Clinical or laboratory factors that can predict abnormal findings on brain MRI in patients diagnosed with CPP have not yet been identified. Some researchers reported that basal luteinizing hormone (LH) and peak LH were statistically significantly increased when CNS abnormalities were present.…”
mentioning
confidence: 99%
“…Several researchers have reported the prevalence of CNS abnormalities detected on brain MRI in CPP [ 4 - 6 ]. Clinical or laboratory factors that can predict abnormal findings on brain MRI in patients diagnosed with CPP have not yet been identified.…”
mentioning
confidence: 99%